The Role of Central Banks in Sustaining Economic Recovery and in Achieving Financial Stability - SIREGAR, Reza Yamora; LIM, Vincent Choon Seng (Journal of Advanced Studies in Finance; Vol 1 No 1 (2010): JASF Volume I Issue 1 Summer 2010, 2010)
Whenever a financial crisis occurs, threatening a possible financial meltdown, central banks have to be at the forefront in combating, neutralizing the crisis and restoring financial stability and economic growth. In this regard, the present sub-prime crisis which originated from the US highlights a few key issues for the SEACEN group of central banks. This paper reviews the policy responses to the crisis which include exit policy strategies from stimulus monetary packages. To strengthen the soundness of the financial system going forward, the paper also highlights counter-cyclical and macroprudential regulations that central banks need to actively look into.